Refuerzo pedagógico como herramienta didáctica para potenciar la motricidad fina de los niños de educación inicial en la escuela Juan e. Verdezoto de la ciudad de Babahoyo provincia de los Ríos - Moreno Miranda, Karina (2021)
This research work carried out on pedagogical reinforcement as a didactic tool used by teachers to enhance the fine motor skills of children in early childhood education at the Juan E. Verdozoto School in the city of Babahoyo in the province of Los Ríos, raised the work proposal on the didactic tools handled in the learning environment such as the classroom, which is based on the primary need to improve fine motor skills through the design of collaborative workshops with daily activities for the benefit of children from 3 to 4 years of initial education age. In this way, it will be possible to potentiate the strengthening in the educational and family interaction of the children, considering the stage of the initial education as the fundamental age for the motor development and the growth of the same, allowing the identification of each process of imitating, recognizing and discovering the behavior of the docents in the family and social environment within the educational area. The methodology of the research carried out is determined as the objective of diagnosing pedagogical reinforcements as a didactic tool and its influence to enhance the fine motor skills of children in initial education at the Juan E. Verdozoto School.